Intracellular ATP Delivery Causes Rapid Tissue Regeneration via Upregulation of Cytokines, Chemokines, and Stem Cells - Mo, Yiqun (Front Pharmacol, 2020)
We have reported accelerated wound healing induced by intracellular ATP delivery in rabbits, through early massive accumulation, in situ proliferation, and M2 polarization of macrophages. Granulation tissue started to grow within first 24 h of treatment and continued the growth till the wound cavity is completely covered. However, the mechanisms underlying this macrophage response are totally unclear because no one has ever reported this before. In this study, we performed a preliminary exploration of the possible mechanisms by focusing on the roles of cytokines, growth factors, and stem cells in this process. Among the 33 adult rabbits, 18 were used for cytokine measurements and the remaining were used for histological and immunohistochemical studies. Four wounds were created on the ventral side of each ear. Two wounds on one side were treated with ATP-vesicles (10 mM ATP), and the other two were treated with controls (normal saline or Regranex). Dressing changes were made daily and the rabbits were sacrificed at 5 h, 12 h, and 1, 2, 3, 4, 6, 9, 15, and 26 days after wounding. Tissue samples were analyzed for cytokines and growth factors using real-time PCR and immunohistochemical staining. The control wounds showed an immediate increase in proinflammatory cytokines after wound creation but no further increase after this initial spike. The growth factor levels in the control wounds remained unchanged throughout the study. Conversely, the wounds treated with ATP-vesicles showed significantly higher expression of MCP-1 and stem cell markers (CD44, CD106, CD146, and CD34) at day 1, significantly higher IL-1β and TNF-α expression from day 1–4, and significantly higher VEGF-A, VEGF-D, and VEGFR-2 expression from day 4–6 when compared to the controls. The significant upregulation of these factors corresponded to the very early and rapid macrophage accumulation, in situ proliferation, and M2 polarization, resulting in unprecedented rapid granulation tissue generation due to direct macrophage collagen production and neovascularization.